Dampak Kegiatan Perkebunan Kelapa Sawit Dalam Peningkatan Ekonomi Masyarakat Di Desa Sungai Payang Kecamatan Loa Kulu Kabupaten Kutai Kartanegara - Heru Suprapto; Shopia Shopia; Fahmi Fahmi (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2019)
Abstract :One of the villages affected by oil palm plantation activities is Sungai Payang Village, Loa Kulu District, Kutai Kartanegra Regency. Sungai Payang Village, Loa Kulu Sub-District has an area of approximately ± 44.736  KM² which is directly adjacent to Margahayu Village in the north, Jembayan Village in the east and Loa Janan Village in the south. Sungai Payang village has a family head (KK) of 780 KK, with details of the population of 1.482 people and 1,270 women, so that the total population of Sungai Payang Village, Loa Subdistrict is 2,740 people with the number of neighbors of the Rukun Tetangga ( RT) as many as 21 RT. The purpose of this study was to find out among other things: 1) the extent of the impact of oil palm plantation activities on improving the economy of the community, 2) the extent of economic impacts affecting the economic development of rural communities. The existence of oil palm plantations in the Sungai Payang Village community has meaning and benefits for the surrounding community, and other facilities can also be felt separately by other communities. Oil palm plantations can be said to have the meaning of supporting the economy of the surrounding community so that it has value and benefits for the local community. PT. Niagamas Gemilang is very useful because the existence of oil palm plantations affects the economic conditions of the community. Keywords: Impact of Oil Palm Plantation, Increasing Community Economy